Six-Month Outcomes of Post-ARDS Pulmonary Fibrosis in Patients With H1N1 Pneumonia - Gao, Jing; Chu, Weili; Duan, Jiali; Li, Junlu; Ma, Wentao; Hu, Chunling; Yao, Mengying; Xing, Lihua; Yang, Yuejie (Frontiers in Molecular Biosciences, 2021)
Objective With improving short-term mortality in ARDS, understanding survivors’ post-hospitalisation outcomes is increasingly important. Our aim was to evaluate the outcomes of 69 survived patients with H1N1 pneumonia, with severe clinical features and abnormal radiological findings who developed post-ARDS pulmonary fibrosis. Materials and methods 280 inpatients with a diagnosis of H1N1 infection confirmed by pharyngeal swab or sputm test. We collected the data from January 2018 to January 2020 in the First Affiliated Hospital of Zhengzhou University and the Sixth People's Hospital of Zhengzhou . Of these, 232 patients had CT findings indicating pulmonary fibrosis after influenza and 69 patients survived. Six months after diagnosis , the 69 patients who had survived were interviewed and underwent physical examination, CT scan,six minute walk test, and quality-of-life evaluation (SF-36). We analyzed baseline variables and Six-month outcomes of post-ARDS pulmonary fibrosis in patients with H1N1 pneumonia. Results Of the 69 survived patients with post-ARDS pulmonary fibrosis, 24 female and 45 male, mean age was 53.7±16.8 years, 18 patients (26%) had no underlying disease, 14 (20%) patients had more than one underlying disease. The distance walked in six minutes increased from a average of 451.9 meters at 3 months to 575.4 meters at 6 months, mean SF-36 physical function increased from a average of 75.3 at 3 months to 77.5 at 6 months,the average CT score was decreased from 31.3 at 3 months to14.8 at 6 months. Treatment with systemic corticosteroid , patients with underlying disease are associated with CT score and the distance walked in six minutes. Conclusion Among the survivors with pulmonary fibrosis after H1N1 influenza , the 6-minute walk test and CT scores of the patients after 6 months were continuously affected. Distance walked in six minutes and imaging findings improved during the first 6 months especially for those with ARDS. The H1N1 pneumonia survivors had impaired HRQoL scores that were lower than those of a sex- and age-matched control population. Keywords ARDS, Fibrosis, CT, H1N1 pneumonia, outcome